Content Analysis of Resilience Indicators for Mainstreaming Resilience into Semarang City's Development Planning Policies - Tresnasari Ratnaningtias; Wiwandari Handayani (The Indonesian Journal of Planning and Development, 2020)
Resilience assessment has been conducted in Semarang City by two different organizations using two different methods, i.e., City Resilience Index (CRI) and Urban Community Resilience Assessment (UCRA) in 2017 and 2018. Based on the result of those resilience assessments, it reveals that some of the resilience indicators are not suitable for local conditions in Semarang City regarding development planning policies. City strategic planning is a mid-term development planning policy with a combination of sectoral planning and comprehensive planning to budgeting process of the local government programs. It also includes local government performance indicators that reflect the level of good governance and lead to enhance city resilience. Hence, indicators in city strategic planning also can be considered as resilience indicators. All of this implies that city strategic planning describes the local government already uses resilience thinking in its strategies, policies, and programs. However, city resilience encompasses many aspects and more complex. This study aims to identify between CRI and UCRA, which method having resilience indicators that are compatible, applicable, and suitable for Semarang’s city strategic planning. CRI and UCRA use different methods and aim at different scopes when assessing resilience in the city. The results of the content analysis on the document of development planning policies, such as the 2016-2021 Semarang’s city strategic planning and Revision of the 2016-2021 Semarang’s city strategic planning, highlight the similarities and differences between CRI and UCRA. It reveals that CRI’s resilience indicators are more compatible, applicable, and suitable for Semarang’s city strategic planning rather than UCRA’s resilience indicators.